Another creature : poems - Gemin, Pamela, 1954- (University of Arkansas Press poetry series., 2010)
Pamela Gemin teaches at the University of Wisconsin Oshkosh and is author of the poetry collection, Vendettas, Charms, and Prayers. She is also the editor of three poetry anthologies including Sweeping Beauty: Women Poets Do Housework. Her poems and anthologies have been featured on NPR's Morning Edition, All Things Considered, and Writer's Almanac.